Peruvian non-university higher education: paperwork management and its implication in job placement - Bellido De La Cruz, Vilma María Fe (2021)
The objective was to analyze the management of procedures and its implication in the labor insertion of graduates of the Avansys Private Technological Higher Education Institute; To achieve this, the methodology of qualitative evaluation with The Most Significant Change was used. Evidence that 27.3% were better qualified for a job position by having the title and 84.6% consider it necessary to obtain the title to enter the job market. It was concluded that the management of the institute's degree hinders the employment of graduates. The factor that makes the process difficult is the high cost and the delay in the process that exceeds the established time.